Morphophysiology of Andropogon gayanus Kunth with organic and mineral fertilization in three vertical layers - Vantini, Paola Pedroso (2008)
The morphophysiological characteristics of the andropogon grass, Andropogon gayanus Kunth cv. Planaltina (Poaceae) with four manure treatments (control; 25 kg N/ha/cutting date; 50 kg N/ha/cutting date and 20 t/ha of cattle manure applied after each cut), were evaluated. There were 28 and 42-day cut intervals within two evaluation periods (84 and 168 days), sampled in three layers (0.20-0.40 m; 0.40-0.60 m; > 0.60 m). Complete randomized block design in a split-split-plot arrangement has been used. Highest values of total dry mass and dry mass of stem were reported in the lowest layer (0.20-0.40 m). The upper layers had higher leaf dry mass (0.40-0.60 m and > 0.60 m), higher leaf area and consequently higher leaf/stem ratio. The four fertilization treatments were not significantly influential on the characteristics of the grass analyzed in this research.